Impacts of groundwater depth and tree age on the non-structural carbohydrates of Haloxylon ammodendron - Lan Peng; Guangyou Hao; Hui Liu; Hui Shen; Xiaobing Zhou; Yongxin Zang; Jing Zhang; Yuanming Zhang (Plant Stress)
Nonstructural carbohydrates (NSC) are important substrates for plant growth and metabolism, and their concentration reflects the plant's ability to adapt to environmental changes. Although the response of NSC to changes in water availability has been extensively studied, it is still not fully understood whether this response is modulated by tree ages and organs. This study investigates Haloxylon ammodendron (C.A. Mey.) Bunge ex Fenzl, the dominant species in the Gurbantunggut Desert in the Uyghur Autonomous Region of China. Utilizing the natural topographic conditions characterized by a gradual increase in groundwater depth from the desert edge to the hinterland, we collected samples of different age classes of H. ammodendron along a groundwater depth gradient of 3, 7, 10, and 14 m. We measured the total concentrations of non-structural carbohydrates (NSC) and its components soluble sugar (SS) and starch (ST) in the assimilative twigs and stems. The results showed that the assimilative twigs of H. ammodendron exhibited higher NSC concentrations at the site with the deepest groundwater, while the other three sites showed similar NSC concentrations. Furthermore, as groundwater depth increased, the concentrations of SS in the assimilative twigs increased, whereas ST concentrations decreased. Similarly, the concentrations of SS in the stems also increased at sites with deeper groundwater. The NSC concentrations in the assimilative twigs were significantly affected by groundwater depth, while variations in stem NSC were primarily driven by plant age. In younger trees, higher soluble sugars concentrations in the stem may enhance water transport efficiency, whereas older trees tend to store more NSC to alleviate drought stress. Overall, elevated nonstructural carbohydrate concentrations contributed to greater drought resilience in H. ammodendron. These results suggest that different age classes of H. ammodendron exhibit distinct physiological responses to decreasing groundwater depth. The varying requirements for soluble sugars and starch in H. ammodendron help to partially mitigate the adverse effects of reduced groundwater accessibility. These findings provide important insights into the physiological adaptations of H. ammodendron in arid environments and offer a scientific basis for future ecological restoration and management strategies.